Formulation and Characterization of Modified Release tablet of Captopril for the Treatment of Hypertension - Priya Chahal; Ashwani Mishra (Current Research in Pharmaceutical Sciences, 2019)
Modified release formulation has been the first choice for formulators of Pharmaceutical formulation it is due to their versatile potential of releasing the drug in desired rate and release kinetic irrespective of their physiochemical and Biopharmaceutical properties. In this research work an attempt was made to formulate Captopril modified release tablet in order to facilitate its release in desired rate and in optimum concentration , Formulation of Tablet formulation was done by preparing bilayer tablet of the drug in which immediate release layer was optimized by using different concentration of sodium starch glycolate and controlled release tablet was formulated by optimizing the concentration of Hydroxypropyl methyl cellulose K4M then they were united and compressed together to formulate optimized formulation among the prepared formulation batches optimized batch F2 exhibited best results of all the evaluation parameters.